2021
DOI: 10.3390/cancers13246291
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Signatures Predict the Early Asymptomatic Doxorubicin-Induced Cardiotoxicity in Breast Cancer

Abstract: Chemotherapy with doxorubicin (DOX) may cause unpredictable cardiotoxicity. This study aimed to determine whether the methylation signature of peripheral blood mononuclear cells (PBMCs) prior to and after the first cycle of DOX-based chemotherapy could predict the risk of cardiotoxicity in breast cancer patients. Cardiotoxicity was defined as a decrease in left ventricular ejection fraction (LVEF) by >10%. DNA methylation of PBMCs from 9 patients with abnormal LVEF and 10 patients with normal LVEF were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…SLFN12 and IRF6 were hypermethylated and transcriptionally downregulated after the first cycle of chemotherapy compared to the baseline in all treatment groups ( IRF6 p = 0.8837 normal LVEF; IRF6 p = 0.8119 abnormal LVEF; SLNF12 p = 0.5718 normal LVEF; SLNF12 p = 0.8575 abnormal LVEF). Decrease in LVEF by >10% or LVEF < 50% compared to baseline Bauer et al, 2021 [ 293 ] High-throughput proteomic profiling using plasma samples Case/control pairs 1 and 2 Case/control pair 3 Validation study of 35 participants DOX plus cyclophosphamide followed by trastuzumab and paclitaxel. ECHO at baseline, after DOX treatment completion and every 3 months of trastuzumab treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SLFN12 and IRF6 were hypermethylated and transcriptionally downregulated after the first cycle of chemotherapy compared to the baseline in all treatment groups ( IRF6 p = 0.8837 normal LVEF; IRF6 p = 0.8119 abnormal LVEF; SLNF12 p = 0.5718 normal LVEF; SLNF12 p = 0.8575 abnormal LVEF). Decrease in LVEF by >10% or LVEF < 50% compared to baseline Bauer et al, 2021 [ 293 ] High-throughput proteomic profiling using plasma samples Case/control pairs 1 and 2 Case/control pair 3 Validation study of 35 participants DOX plus cyclophosphamide followed by trastuzumab and paclitaxel. ECHO at baseline, after DOX treatment completion and every 3 months of trastuzumab treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Bauer et al, 2021 [ 293 ], demonstrated that the methylation status of peripheral blood mononuclear cells (PBMCs) could predict the LVEF reduction after treatment with DOX in HER2-negative breast cancer patients. Specifically, a total of 14,883 differentially methylated CpGs were identified at baseline and were associated with a reduction in LVEF in response to DOX treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The following analyses were conducted using a publicly available dataset, which has previously been published [ 25 ]. Briefly, a total of 19 patients with breast cancer who underwent chemotherapy treatment at the Winthrop P. Rockefeller Cancer Institute at the University of Arkansas for Medical Sciences were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…DOX can lead to the downregulation of DNA methyltransferase 1 (DNMT1) enzyme activity, resulting in a decrease in DNA methylation [36]. For example, in one study, significantly differentially methylated regions were found in SLFN12, IRF6, and RNF39 genes and promoters in patients with LVEF abnormalities after DOX treatment [37].…”
Section: Genomicsmentioning
confidence: 99%